Reflections on brand image: the influence of donor ideal and perceived charity brand congruence on charitable giving - Crawford, Elizabeth Crisp; Jackson, Jeremy Jay (Frontiers in Communication, 2025)
IntroductionNonprofit branding in today’s digital and social media landscape is increasingly shaped by active audience participation, rather than solely by messaging from the organization. This study investigates how donors’ perceptions of congruence between their ideal and actual charities, measured as donor–brand congruence, influence the amount of charitable giving.MethodsUsing a survey based on the Aaker Brand Personality Scale, participants evaluated both their actual and ideal charities across 15 facets within five brand personality dimensions, including Sincerity, Excitement, Competence, Sophistication, and Ruggedness. Participants also provided demographic data, personality traits, and annual donation amounts.ResultsThe findings reveal that donors perceiving a match between their ideal and actual charity brands self-report more financial contributions. Additionally, age and emotional stability correlated with greater perceived congruence.DiscussionThe results suggest that forming a match between a nonprofit’s actual brand and the audience’s ideal brand can be essential for creating nonprofit brand identities that resonate within a hyper-personalized (tailored to individual preferences), polycentric (influenced by many actors) communications environment. By encouraging donor input and discovering their aspirational values, nonprofits can cultivate authentic connections, strengthen loyalty, and encourage word-of-mouth advocacy for their cause.